Inovasi Pembelajaran Science System Pada Masa Pandemi Covid-19 untuk Menjamin Hak Konstitusi Warga Negara Indonesia: Innovation in Science System Learning During the Covid-19 Pandemic to Guarantee the Constitutional Rights of Indonesian Citizens - Widiastuti, Anita Indah (Seminar Nasional Hukum Universitas Negeri Semarang, 2021)
The accommodation of universal principles in the Miranda Principles into the Indonesian national legal system, as reflected in the formulation of articles of the Criminal Procedure Code such as Article 54, Article 55, Article 56 paragraph (1), and Article 114 of the Criminal Procedure Code, as well as in other legal products such as the Law No. 39 of 1999 and Law no. 12 of 2005, it is a necessity to enforce these principles, and one of them is through the provision of legal assistance. Although formally, the provision of legal assistance has been regulated in the Indonesian legal system, but the provision of legal assistance doesn't always run as it should in practice, especially during the current Covid-19 pandemic. The main purpose of this study focuses on an analysis related to the extent to which legal assistance is provided in upholding the Miranda Principles, as well as how to optimize the provision of legal assistance during the Covid-19 pandemic in the context of protecting citizens' constitutional rights. In this study, the method used is normative research using a statutory, conceptual, and case approach. The results of the study indicate that the enforcement of the Miranda Principles through the provision of legal aid assistance has not been optimal yet. So that, the repressive approach is still needed, such as giving administrative sanctions to lawyers who still haven't carry out their obligations optimally in providing legal assistance.